2021
DOI: 10.1007/s11764-021-01065-z
|View full text |Cite
|
Sign up to set email alerts
|

Use of active video games with or without videoconferencing on health outcomes in adolescent and young adult cancer survivors: a systematic review

Abstract: Purpose Adolescent and young adult (AYA) cancer survivors experience greater functional deficits compared to non-cancer peers or older survivors with a similar diagnosis. Physical activity (PA) is a key strategy for mitigating functional decline, and motivation and peer support are critical PA facilitators in AYA cancer survivors. Active video games (AVGs) may be a "gateway" method to promote PA. Further, integrating AVGs into group videoconferencing, a medium used by AYAs to socialize, can capitalize on peer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…The remaining 134 reviews met eligibility criteria and were included in the synthesis. 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 134 reviews met eligibility criteria and were included in the synthesis. 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 …”
Section: Resultsmentioning
confidence: 99%
“…Many reviews indicated that a meta-analysis was not done due to heterogeneity of methods and outcomes. 13 , 15 , 18 , 21 , 23 , 29 , 40 , 45 , 46 , 49 , 60 , 65 , 69 , 74 , 75 , 86 , 88 , 89 , 90 , 97 , 100 , 104 , 110 , 116 , 118 , 131 , 134 …”
Section: Resultsmentioning
confidence: 99%
“…These tools may use videogames developed for commercial entertainment or games specifically designed for health interventions. The game-playing experience is very absorbing, and virtual reality devices and smartphones enhance adherence to the therapy and reduce some of the negative aspects of the disease and its treatments [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…39 In another systematic review, in some studies, the physical activity interventions using video games with or without videoconferencing improved the quality of life of AYA survivors. 38 In another systematic review and meta-analysis, improvements in the psychosocial and emotional health of childhood and AYA cancer survivors were observed after the technology-based interventions. 18 In the intervention study conducted with children and adolescent survivors (aged 9-16 years), which was performed by a specialist nurse who has extensive experience in caring for children with cancer, it was determined that adventure-based training (4-day integrated adventure-based training to promote physical activity and reduce fatigue, and adventure-based training activities; the program was implemented in small groups with a maximum of 12 participants per group at a campsite on 4 days over a 12-month period, conducted in China) significantly increased the quality of life in the LTFU, and the intervention group showed better quality of life than the control group at 12 months.…”
mentioning
confidence: 99%
“…Conclusive evidence has not been presented in the literature on the impact of technology-based health promotion and psychosocial interventions on CCS. 38 In a systematic review evaluating 4 studies, digital self-management interventions (eg, physical activity) were not effective on the quality of life of childhood cancer survivors. 39 In another systematic review, in some studies, the physical activity interventions using video games with or without videoconferencing improved the quality of life of AYA survivors.…”
mentioning
confidence: 99%